Time-sharing performance of choice-response tasks: factor structure and age differences - Šverko, Branimir; Maslić Seršić, Darja; Jerneić, Željko Gurdulić-Šverko, Anja (1994)
The present study sought support for the notion of time sharing ability by analyzing time-sharing and single-task performance reveals different factor structures and exhibits differential relations to the subjects' age. A total of 80 truck drivers, ranging in age from 20 to 61 years, participated in the study. They performed four computerized reaction-time tasks both singly, one by one, and concurrently, in different two-task combinations. The analysis of the results proves that the performance under solitary and time-sharing conditions reveals different features: (a) in factor analysis they load on separate factors, and (b) in relation to the subjects' age they show a different decline, the time-sharing performance declining faster. This indicates that time-sharing performance reveals some reliable individual differences which are not manifested in the same tasks when performed singly and, thus, supports the notion of time-sharing ability.
Časopis je naveden u Pravilniku iz NN/97
Projekt MZOS
ENG